ANALISIS MAKRO DAN MIKROSTRUKTURAL LIRIK LAGU”ANDAI AKU GAYUS TAMBUNAN” - NFN Nursyamsi (Balai Bahasa Sulawesi Tengah, 2013)
The song is the universal language which becomes the link of the expression of heart feeling and its background situation. As an art, music is not only to entertain but also has function as communiation medium which has been reflected by the song’s lyrics. As the text, the song has theorganized sign system, based on the codes which has been reflected the certain values, attitude, and faith. Each of (communication) message in song has two grades of meaning, that are macrostructural and microstructural meaning. Those grades of meaning in the discourse of song’s lyric which is written by Bona Paputungan is revealed on this study. The methods which is applied on this study are literature and analytics-descriptive ones. The study is written in the narrative text. In the result of macrostructural analysis, it is shown that social and situational context in the song os about the misery of a convict. The place setting of the song is on the jail, while the time setting is started fromMarch 11 and ended in October, 7. The macrostructural analysis is that song’s lyrics have many grammatical aspects such as references, eliptical, and conjunctions. The lyrics also has lexical aspects such as collocation and repetition.